Analisis SDM dan Kondisi Lingkungan di Perumahan Pesona Laguna 1 Depok Blok D RT 04/RW 20 - Rio Ramadhan; Susi Rohani; Nurkhofifah Amini; Riska Olivianti (Jurnal Insan Pendidikan dan Sosial Humaniora, 2026)
This study aims to analyze the condition of human resources (HR) and the environment in Pesona Laguna 1 Housing Complex, Depok, Block D, RT 04/20, using a descriptive qualitative approach through field observations, informal interviews, and documentation. The results indicate that the condition of HR is quite good and has the potential to develop, indicated by adequate access to education, a variety of jobs, and harmonious social relations. The environmental conditions are also relatively clean and well-managed, although there are still problems with flooding during heavy rainfall caused by limited water channel capacity and a lack of discipline among some residents in disposing of waste. Flood management is generally carried out through community service cleaning water channels, which reflects a fairly high level of public awareness in maintaining environmental cleanliness. However, HR development still faces obstacles such as limited ongoing training programs and a lack of support for individual potential. Therefore, efforts are needed to improve the quality of HR and environmental management, particularly in improving drainage systems and flood prevention, in order to achieve optimal and sustainable development.